2018
DOI: 10.1038/s41556-018-0127-y
|View full text |Cite
|
Sign up to set email alerts
|

Senescence-associated ribosome biogenesis defects contributes to cell cycle arrest through the Rb pathway

Abstract: Cellular senescence is a tumour suppressor programme characterized by a stable cell cycle arrest. Here we report that cellular senescence triggered by a variety of stimuli leads to diminished ribosome biogenesis and the accumulation of both rRNA precursors and ribosomal proteins. These defects were associated with reduced expression of several ribosome biogenesis factors, the knockdown of which was also sufficient to induce senescence. Genetic analysis revealed that Rb but not p53 was required for the senescen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
103
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(118 citation statements)
references
References 44 publications
13
103
2
Order By: Relevance
“…At this time, it is unclear why there is such a specific activation of the cholesterol biosynthesis pathway by shLSG1 and why this signature is also so prevalent in OIS and other forms of senescence. A recent study identified accumulation of the ribosomal 40S subunit protein RPS14 as a mechanism contributing to senescence in response to multiple stimuli (Lessard et al, 2018). Unlike our p53-dependent response, the response to RPS14 was Rb-dependent, indicating that it is mechanistically distinct.…”
Section: Discussioncontrasting
confidence: 70%
“…At this time, it is unclear why there is such a specific activation of the cholesterol biosynthesis pathway by shLSG1 and why this signature is also so prevalent in OIS and other forms of senescence. A recent study identified accumulation of the ribosomal 40S subunit protein RPS14 as a mechanism contributing to senescence in response to multiple stimuli (Lessard et al, 2018). Unlike our p53-dependent response, the response to RPS14 was Rb-dependent, indicating that it is mechanistically distinct.…”
Section: Discussioncontrasting
confidence: 70%
“…It has also been suggested that dysregulation of RPs supports the hyperproliferative cancer cell phenotype 21 compounds suggests that tumour cell addiction to enhanced ribosomal biosynthesis could be exploited for therapeutic gain, and our findings indicate that this could be achieved through a RSIS pro-senescence strategy. Both our work and the findings of Lessard et al 16 indicate that a small molecule which perturbs ribosomal protein homeostasis could be effective at selectively engaging a p16-dependent senescence programme in cancer cells. In support of this, we present evidence of co-ordinated dysregulation of our two most potent RP hits, RPS3A and RPS7.…”
Section: Lessard Et Al Recently Demonstrated That Senescence-associasupporting
confidence: 71%
“…contribute to cell cycle arrest through the Rb pathway which is associated with altered nucleolar morphology 16 . In summary, we show that RP knockdown initiates a p16-mediated senescence programme in a p53-independent and cancer-specific manner, and paves the way for pro-senescence therapies aimed at re-engaging this potent tumour suppressor mechanism in highly aggressive breast cancer subtypes, such as BLBC.…”
Section: Lessard Et Al Recently Demonstrated That Senescence-associamentioning
confidence: 99%
“…It should also be mentioned that senescence of tumor cells lacking functional cell cycle inhibitors may be explained by defects in senescence-associated ribosome biogenesis and concomitant accumulation of rRNA precursors and ribosomal proteins. From the mechanistic point of view, senescent cells accumulate the ribosomal protein S14 (RPS14 or uS11) in the soluble non-ribosomal compartment, where it binds and inhibits cyclin-dependent kinase 4, leading to the inhibition of retinoblastoma protein phosphorylation, cell cycle arrest, and senescence [127].…”
Section: Drug-induced Senescence Of Cancer Cellsmentioning
confidence: 99%